Dilemma of Data Driven Technology Regulation : Applying Principal-agent Model on Tracking and Profiling Cases in Korea - 이유현; 정일영 (디지털융복합연구, 2020)
This study analyzes the regulatory issues of stakeholders, the firm, the government, and the individual, in the data industry using the principal-agent theory. While the importance of data driven economy is increasing rapidly, policy regulations and restrictions to use data impede the growth of data industry. We applied descriptive case analysis methodology using principal-agent theory. From our analysis, we found several meaningful results. First, key policy actors in data industry are data firms and the government among stakeholders. Second, two major concerns are that firms frequently invade personal privacy and the global companies obtain monopolistic power in data industry. This paper finally suggests policy and strategy in response to regulatory issues. The government should activate the domestic agent system for the supervision of global companies and increase data protection. Companies need to address discriminatory regulatory environments and expand legal data usage standards. Finally, individuals must embody an active behavior of consent.
Keywords: Technology Regulation; Data Industry; Principal-Agent Model; Tracking; Profiling; 기술규제; 데이터 산업; 주인-대리인 이론; 트래킹; 프로파일링